KERJASAMA INDONESIA - JERMAN DALAM UPAYA MENURUNKAN EMISI GAS RUMAH KACA MELALUI PROGRAM INTERNATIONALE KLIMASCHUTZINITIATIVE (IKI) PERIODE 2013-2015 - Hilda Azharul Fauziyah, (2021)
The establishment of the UNFCCC which initiated the formation of a binding agreement on the obligations of industrialized countries to reduce GHG emissions. Seeing the condition of GHG in Indonesia, which has experienced a significant increase in 2015, making Indonesia, which is an archipelagic country, is vulnerable to the negative impacts of increasing GHG emissions. Germany as an industrial country then launched a program called the Internationale Klimaschutzinitiative (IKI) with an allocation of 120 million euros per year which aims to help developing countries achieve the commitments set out in the Nationally Determined Contribution (NDC). In this context, IKI will help Indonesia to meet Indonesia's national interest regarding the GHG emission reduction target listed in Indonesia's NDC, which is 29% through the business as usual (BAU) scenario, and increase up to 41% GHG emission by 2030 with international support. Since 2008, IKI has overseen 29 bilateral projects between Germany and Indonesia and has made a real contribution in helping Indonesia reduce GHG emissions, as evidenced in 2016 Indonesia has succeeded in reducing GHG emissions which in the previous year had increased sharply. Based on this, this article will describe the implementation of cooperation projects built between Indonesia and Germany under the Internationale Klimaschutzinitiative (IKI) scheme related to efforts to reduce GHG emissions in Indonesia in the period 2013-2015. The discussion in this article will be related to the theory of national interest, the concept of bilateral cooperation, the concept of climate change and the concept of implementation, which will later become a reference for answering research questions, which are related to "How to Implement Cooperation between Indonesia and Germany in an effort to reduce GHG emissions through program Internationale Klimaschutzinitiative (IKI) for the period 2013-2015?